Raising of Microvascular Flaps A Systematic Approach - Wolff, Klaus-Dietrich.; Hölzle, Frank; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
Raising of Microvascular Flaps provides all those dealing with microsurgical tissue transfer, i.e. plastic surgeons, ENT surgeons, trauma surgeons, and oral and maxillofacial surgeons with all they need to know in their daily practice. The systematic approach of this operative manual is based on photographs of perfect quality showing cadaver preparations alongside with explanatory colour drawings to even enhance the understanding of the anatomy through 3D perspectives and by also showing structures that are hidden in preparation. A clear didactic structure and perfect artwork supply the surgeon with invaluable guidelines for his daily work. Focusing on comprehensive, precise and teaching information, this text atlas is highly instructive.
Radial forearm flap: Development and Indications; Anatomy; Advantages and Disadvantages; Flap Raising; Comments -- Lateral Arm Flap: Development and Indications; Anatomy; Advantages and Disadvantages; Flap Raising; Comments -- Anterolateral Thigh / Vastus Lateralis Flap: Development and Indications; Anatomy; Advantages and Disadvantages; Flap Raising; Myofascial Flap; Comments -- Latissimus Dorsi Flap: Development and Indications; Anatomy; Advantages and Disadvantages; Flap Raising; Comments -- Scapular Flap: Development and Indications; Anatomy; Advantages and Disadvantages; Flap Raising; Comments -- Fibula Flap: Development and Indications; Anatomy; Advantages and Disadvantages; Flap Raising; Comments -- Iliac Crest Bone Flap: Development and Indications; Anatomy; Advantages and Disadvantages; Flap Raising; Comments -- Literature.
Keywords: Oral surgery; Maxillofacial surgery; Plastic surgery; Otorhinolaryngology; Otolaryngologic surgery; Oral and Maxillofacial Surgery; Plastic Surgery; Otorhinolaryngology; Head and Neck Surgery